The mise-en-scène of ’minor’ history in Mangiamele’s Il contratto - Lampugnani, Raffaele (Spunti e Ricerche, 2016)
Giorgio Mangiamele, regarded as the most significant first-generation Italo-Australian filmmaker, produced films in the decade from 1953 until 1963 which deal with the Italian diaspora, focusing quite specifically on distinct phases of the Italian migration experience in Australia. Il contratto is a work of significant sociological and historical value, or, as Quentin Turnour described it, "one of the most extraordinary independent feature productions in Australian cinema history". It is also Mangiamele’s film that would best fit what Gilles Deleuze and Félix Guattari theorised as "minor literature", an expression of "that which a minority constructs within a major language", and which is "affected with a high coefficient of deterritorialization".